Review of the IMF's Communications Strategy. (Policy Papers; Policy Paper ;, 2014)
The framework guiding the IMF's communications-established by the Executive Board in 2007-has enabled the institution to respond flexibly to the changing global context. The framework is based on four guiding principles: (i) deepening understanding and support for the Fund's role and policies; (ii) better integrating communications into the IMF's daily operations; (iii) raising the impact of new communications materials and technologies; and (iv) rebalancing outreach efforts to take account of different audiences. In addition, greater emphasis has been placed on strengthening internal communications to help ensure institutional coherence in the Fund's outreach activities. Continued efforts are needed to strengthen communications going forward. Several issues deserve particular attention. First, taking further steps to ensure clarity and consistency in communication in a world where demand for Fund services continues to rise. Second, doing more to assess the impact of IMF communications and thus better inform efforts going forward. Third, engaging strategically and prudently with new media-including social media.